Quantifying Marine Sedimentary Carbon: A New Spatial Analysis Approach Using Seafloor Acoustics, Imagery, and Ground-Truthing Data in Scotland - Hunt, Corallie; Demšar, Urška; Dove, Dayton; Smeaton, Craig; Cooper, Rhys; Austin, William E. N. (Frontiers in Marine Science, 2020)
Marine sediments are important repositories of particulate organic matter, effectively burying organic carbon (OC) over geological timescales thus providing a climate regulation service. However, the spatial distribution of this marine sedimentary OC store is not well constrained. In this study we leverage a high resolution multibeam echosounder (MBES) survey taken at Loch Creran, a model fjordic site on the west coast of Scotland, to develop a new methodology for predicting the distribution of OC in surface sediments. Using an integrated approach, we combine use MBES survey, video imagery and ground-truthing data to produce a high-resolution (2 m x 2 m) map of surficial carbon and calculate a 10 cm stock. We find that the backscatter survey reliably uncovers a heterogeneous seabed and that OC correlates strongly with the MBES backscatter signal as a function of sediment composition. We estimate that there are approximately 12,346 ± 2,677 tonnes of OC held within the top 10 cm of mixed sediments across the MBES survey area (7.96 km2; 60% of the total area), upscaled to 20,577 ± 4,462 t of OC across Loch Creran (13.27 km2). Normalised by area, we find that mixed fine sediments with small fractions of sand and gravel are more effectivehold more carbon OC stores than homogenous fine sediments. This initial work proposes a novel methodological approach to using high resolution MBES surveys to improve the spatial mapping of sedimentary C carbon (C) and identification of C hotspots, enabling consideration of this resource in sedimentary carbon accounting, seabed management and climate mitigation strategies.